1997
DOI: 10.1093/ageing/26.3.185
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the cough reflex in young and elderly subjects

Abstract: The sensitivity of the cough reflex appears to be significantly reduced in elderly subjects. This may increase the risk of aspiration and bronchopulmonary infection in old age, even in the absence of respiratory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 24 publications
2
34
1
4
Order By: Relevance
“…Central nervous system disorders, dementia and poor PS were significantly more frequent in patients with NHCAP compared with those with CAP in both hospitals. Previous studies (6,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) as well as in the current study suggested that a high frequency of aspiration pneumonia is possibility related to older age, poor PS, dementia and previous brain infarction in Japan. Anaerobes, Streptococcus anginosus group, S. pneumonia, H. influenzae and S. aureus, are thought to be important pathogens in aspiration pneumonia (12).…”
Section: Discussionsupporting
confidence: 74%
“…Central nervous system disorders, dementia and poor PS were significantly more frequent in patients with NHCAP compared with those with CAP in both hospitals. Previous studies (6,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) as well as in the current study suggested that a high frequency of aspiration pneumonia is possibility related to older age, poor PS, dementia and previous brain infarction in Japan. Anaerobes, Streptococcus anginosus group, S. pneumonia, H. influenzae and S. aureus, are thought to be important pathogens in aspiration pneumonia (12).…”
Section: Discussionsupporting
confidence: 74%
“…Thus, the absence of any serious cardiac event in our population could likely be explained by the absence of sedation, by accurate and quick oxygen supplementation during FOB, by the professional skill and experience of the bronchoscopist and by the amount of lidocaine administered to the patients. Although the cough reflex is reduced in the elderly [38], we did not change their premedication.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that reduced bradykinin and substance P levels repress cough reflex and therefore increase the risk to develop pneumonia [12]. As previously reported, a suppressed cough reflex in elderly individuals increases the risk of aspiration and respiratory infection [3]. Use of ACE inhibitors was also found to improve swallowing reflex in 22 elderly individuals with aspiration pneumonia but did not increase the normal reflex in healthy subjects [36].…”
Section: Discussionmentioning
confidence: 78%
“…Available data implicate that pathogenesis of pneumonia correlates with attenuation of cough reflex [2,3], an important defensive respiratory reflex that protects the lungs from inhalation or aspiration of potentially injurious substances and clears excess secretions [4,5]. Basic investigation has shown that bradykinin and substance P sensitize the sensory nerves of the airways and enhance the cough reflex, which may have a protective role on the tracheobronchial tree [6].…”
Section: Introductionmentioning
confidence: 99%